Barriers to accessing and utilising under-five primary health care services in Vhembe District - Livhuwani Tshivhase; Idah Moyo; Sophie M. Mogotlane; Sophy M. Moloko (African Journal of Primary Health Care & Family Medicine, 2024)
Background: Sub-Saharan Africa continues to be the region with the highest under-five mortality rate globally, with 74 deaths per 1000 live births. Even though under-five child primary health care (PHC) services are free in South Africa, accessing such services remains challenging. Children under 5 years reportedly die from common illnesses such as pneumonia, diarrhoea and malaria, which are treatable in PHC facilities.